SYNTHESIS OF ACTIVATED CARBON FROM SORGUM STEM WASTE (Sorghum bicolor (L.) Moench) AS RHODAMIN B ADSORBENT WITH VARIATIONS OF NaOH ACTIVATOR CONCENTRATION - Matius Stefanus Batu; Roswita Teti; Maria Magdalena Kolo (Molluca Journal of Chemistry Education (MJoCE), 2025)
Rhodamine B is a synthetic dye commonly used, especially in the textile industry. Excessive entry of Rhodamine B into the environment can alter the pH of water, which can disturb microorganisms and animals living in aquatic environments. One way to address the pollution of Rhodamine B is by using activated carbon from sorghum stalk waste. Activated carbon is carbon that has been processed through activation to have pores with a very large surface area, thereby enhancing its adsorption capacity. The aim of this study is to determine the characteristics of activated carbon from sorghum stalk waste and to determine the optimum NaOH concentration in the synthesis of activated carbon from sorghum stalk waste as an adsorbent for Rhodamine B dye. The stages in this study include the preparation of sorghum stalk waste samples, carbonization, and activation of the carbon from sorghum stalk waste using NaOH activator with concentration variations of 2, 3, 4, 5, and 6% for 24 hours. The adsorption process was carried out using the activated carbon from sorghum stalk waste to adsorb Rhodamine B dye. The results of the study showed that the characteristics of the activated carbon from sorghum stalk waste had a moisture content of 4-7.3%, ash content of 2.3-7.6%, and an iodine adsorption capacity of 2,410.67-3,427.11 mg/g. The results of the characterization of activated carbon from sorghum stalk waste overall met the Indonesian National Standard (SNI). The optimum NaOH activator concentration for adsorbing Rhodamine B dye was obtained at a concentration of 6%, with an adsorption efficiency of 88.94%.